Adsorption and separation of n-hexane and cyclohexane on the UiO-66 metal–organic framework - Bozbiyik, Belgin; Duerinck, Tim; Lannoeye, Jeroen; De Vos, Dirk E.; Baron, Gino V.; Denayer, Joeri F.M. (Microporous and mesoporous materials, 2014)
•Study of adsorption and separation of n-hexane (nC6) and cyclohexane(cC6) on UiO-66.•Preferential adsorption of cC6 over nC6 is observed in pulse gas chromatography.•cC6 is retained about 5 times longer than nC6.•Adsorption Gibbs energy is more favorable for cyclic compared to linear alkanes.•Breakthrough experiments confirm this unusual preferential adsorption. Adsorption and separation of n-hexane and cyclohexane on the UiO-66 metal organic framework was studied by pulse gas chromatography and vapour phase breakthrough experiments. Vapour phase breakthrough experiments were performed with mixtures of both components, diluted in helium. Experiments were carried out at temperatures between 50 and 200°C, at partial pressures between 0.0024 and 0.05bar and varying mixture composition. In all conditions, separation between both components is observed, with cyclohexane being the most strongly retained component. This unusual preference for adsorbing the more bulky cyclic alkane isomer was further studied by pulse GC measurements at low coverage, at temperatures between 200 and 300°C. These experiments confirm the inverse shape selective behaviour of UiO-66 in the adsorption of linear and cyclic alkanes. Cyclohexane fits better in the cages of UiO-66, leading to a more negative adsorption enthalpy, together with a lower loss of entropy during adsorption as compared to n-hexane.